PEMBINAAN AKHLAKUL KARIMAH PADA SISWA SMA SWASTA AR-RAHMAN KECAMATAN HELVETIA MEDAN - Lubis, Sakban; Syarifuddin; Malik, Mukhlis; Kamil, Muhammad; Devina, Amanda (STAI Pelabuhan Ratu, 2024)
This study aims to describe and analyze in depth about the model of fostering Akhlakul in Ar-Rahman Private High School Students in Helvetia District. Research on Ar-Rahman Private High School Students uses an anthropological approach and this is a qualitative research. Data collection is done by conducting interviews, observation and documentation. Data analysis was carried out with descriptive analytics, namely giving meaning to the data collected, and from that meaning conclusions were drawn. The results showed: that the implementation of moral coaching at Ar-Rahman Private High School Students in Helvetia District has been running well as expected, This can be seen from the daily behavior of students, such as in terms of speaking, both with teachers, friends, and the surrounding community, good manners, then from the way of dressing that looks polite to reflect students, both inside the dormitory and outside the dormitory. Faktor pendukung dalam membina akhlak siswa adalah adanya kerjasama antara pihak madrasah dengan pihak asrama, baik pengasuh maupun pembina, kerjasama dengan semua guru mata pelajaran. While the inhibiting factors in fostering student morals in Ar-Rahman Private High School Students in Helvetia District are lack of support from the family, the environment, students are in the company of their peers who have the same level of ego so that sometimes conflicts often arise.